The Relationship Between Age and Mental Health Among Adults in Iran During the COVID-19 Pandemic - Chen, J. (2021)
The evidence on the predictors of mental health in the COVID-19 pandemic has revealed contradictory findings, which prevent effective screening for mental health assistance. This study aims to identify the predictors of mental health issues, specifically examining age as a nonlinear predictor. Based on a survey of 474 adults using snowball sampling under the COVID-19 pandemic during April 1th–10th, 2020, in Iran, we found that age had a curvilinear relationship with nonsomatic pain, depression, and anxiety. Specifically, it predicted pain, depression, and anxiety disorders, negatively among adults younger than 45 years, yet positively among seniors older than 70 years. Adults who were female, were unsure about their chronic diseases, or exercised less were more likely to have mental health issues. This study, being the first paper to examine age curvilinearly, suggests future research to pay more attention to nonlinear predictors of mental health disorders in the COVID-19 pandemic.